Mathematical Learning with Metacognitive Ability Based on Problems in Solving the Source of Mathematical Stories in SMP Patra Dharma 2 Balikpapan - Rahayu Sri Waskitoningtyas (Variabel, 2018)
This study aims to describe the learning of mathematics with metacognitive ability based on problem solving in solving mathematics story problem in SMP Patra Dharma 2 Balikpapan. The type of this research is qualitative research, while the sampling technique is purposive sample. The results showed that through solving problems in solving mathematical problems, (1) learners will be trained to always involve metacognitive skills from the beginning of solving the problem of mathematics to the end of the form of formulation of answers and evaluate the results of work, (2) learners who have good metacognition skills tend to solve problems of solving problems of mathematical stories that they face well through the mobilization of consciousness and contextual thinking arrangements, and (3) learners are required to mobilize awareness and regulation of thinking (metacognition) through some math problem solving exercise.